Optimization of the Distribution of Zakat Infak Sedekah Funds on the Independence of Mustahik in Economic Program: A Case Study - Nuryani, Rahmah; Nawawi, Kholil; Hakim, Nurman (The Economic Review of Pesantren, 2023)
Islam has five pillars of Islam, one of which is zakat, the potential for zakat if developed optimally from all Islamic communities and managed properly with its management will realize a very large amount of funds and can be used to overcome poverty. This research aims to answer three main problems, namely how the mechanism of LAZ Al Bunyan, on of zakat institution in Bogor City, in distributing zakat funds. This research aims to determine the optimization of the distribution of zakat infaq and shadaqah (ZIS) against mustahik independence in the economic program of Bogor city. This research uses qualitative methods with a descriptive qualitative approach. Data collection techniques include observations, interviews, and documentation. The result of this research is, in the distribution of the Amil Zakat Al-bunyan Institute in Bogor City in distributing zakat, infaq and alms funds using two ways, namely consumptive and productive distribution. The optimization of the distribution of zakat funds, infaq and alms looks at mustahik independence, can be seen from three factors, namely increasing income, business development, and having turned into a muzzaki. The obstacles faced by the Amil Zakat Al-bunyan Institute in the 2021-2022 economic program program are constrained by the covid-19 virus, lack of communication with local RT / RW and very steep locations and usually in the interior.